-4(-2,5-2x)+2(-1,8+1)
-(a+2)+2(4-3a)
..

за спам,бан​

zhenyakulakova zhenyakulakova    1   30.03.2021 09:48    0

Ответы
westt westt  29.04.2021 09:59

1) Давайте упростим шаг за шагом.

−4 (−25−2x) +2 (−18 + 1)

Распространять:

= (- 4) (- 25) + (- 4) (- 2x) +2 (−18 + 1)

= 100 + 8x + −34

Объедините похожие термины:

= 100 + 8x + −34

= (8x) + (100 + −34)

2) Давайте упростим шаг за шагом.

- (а + 2) +2 (4−3а)

Распространять:

= −a + −2 + (2) (4) + (2) (- 3a)

= −a + −2 + 8 + −6a

Объедините похожие термины:

= −a + −2 + 8 + −6a

= (- a + −6a) + (- 2 + 8)

= −7a + 6

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика